Models at work : a practitioner's guide to risk management - Farid, Jawwad Ahmed; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
This book provides a much needed'middle ground' for risk practitioners who need an in-depth understanding of risk management without excessive formulae or theory. Written to appeal to a broad but financially-minded audience, it provides coverage of risk management and the frameworks commonly applied in the financial services industry.
Keywords: Risk management; Management